Landasan Ideologis: Pancasila, NKRI, dan Pendidikan Islam - Aulia Azizatul Hidayah; Syaifuddin Sabda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Islamic education in Indonesia plays a strategic role in shaping students’ religious character as well as their national identity, and therefore cannot be separated from the ideological foundations of Pancasila and the Unitary State of the Republic of Indonesia (NKRI). Islamic education functions not only as a means of transmitting religious values, but also as a medium for internalizing national ideology in line with the goals of national education. This study aims to analyze the ideological foundations of Islamic education based on the values of tauhid, Pancasila, and NKRI, as well as to examine their relevance to national education policies and curricula. This research employs a qualitative approach using a library research design. The data were obtained from secondary sources, including scholarly books, journal articles, education policy documents, and relevant legislation. Data collection was conducted through documentation studies, while data analysis applied a descriptive-analytical method to systematically examine the interrelationships among concepts. The findings indicate that the ideological values of Pancasila are substantively aligned with Islamic teachings, particularly in the aspects of divinity, humanity, unity, deliberation, and social justice. Within the framework of NKRI, Islamic education contributes significantly to the formation of religious-nationalist character and the strengthening of national integration. The integration of Pancasila values, religious moderation, and Islam rahmatan lil ‘alamin into national education policies and curricula, particularly through the Merdeka Curriculum and the Pancasila Student Profile, reflects a systematic effort to develop Islamic education that is adaptive and contextual. The implications of this study emphasize that strengthening the ideological foundations of Islamic education is a crucial prerequisite for producing learners who are faithful, knowledgeable, morally upright, and responsible citizens of Indonesia.